The Effect of Class Teachers' Self-Efficacy on Inclusive Education Services for Special Needs Children in Inclusive Schools - Nur, Devina Rahmadiani Kamaruddin; Dwirisnanda, Danis Ade; Minarsih, Ni Made Marlin; Ekasari, Diah; Ludfi, Muhammad Kholid Ni’amul; Rosyidah, Amalia Batul (Faculty of Education Universitas Negeri Malang, 2024)
This study aims to understand the Effect of Teachers' Self-Efficacy on Inclusive Education Services for Special Needs Children in Inclusive Schools. The variables studied were Class Teachers' Self-Efficacy as an independent variable (X) and teacher attitudes toward inclusive education services as a dependent variable (Y). The method used is quantitative research, with cluster sampling technique. This research will involve 12 inclusive elementary schools representing the western, eastern, northern, southern and central parts of Surabaya. Participants of this study were teachers from inclusive public elementary school in Surabaya (N = 125). The instrument used to measure teacher efficacy is Teacher Efficacy for Inclusive Practice (TEIP), while Multidimensional Attitudestoward Inclusive Education Scale (MATIES) was used to measure teacher attitudes toward inclusive education service. Processing methods of data analysis in hypothesis testing using regression analysis. The data analysis processing method in hypothesis testing uses regression analysis to test relationships between the independent variable (teacher self-efficacy) and the dependent variable (Special Needs Children service attitudes at school). There is a role of teacher efficacy on teacher attitudes towards inclusive education services. The results of the research show that there is an influence between Class Teacher Self-Efficacy on Special Education Services in Inclusive Schools as indicated by the t-count > t-table (4.016 > 1.657) and by the probability value (p <α; 0.000 < 0.05) , with an influence contribution of 0.16 (16%).